2015
DOI: 10.1093/ntr/ntv083
|View full text |Cite
|
Sign up to set email alerts
|

The Psychometric Performance of the PROMIS Smoking Assessment Toolkit: Comparisons of Real-Data Computer Adaptive Tests, Short Forms, and Mode of Administration

Abstract: Results indicate that the SF and CAT and computer and paper-and-pencil administrations provide highly comparable scores for daily and nondaily smokers, but preference for SF or CAT administration may vary by smoking domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The fixed form scales typically range from 4 to 8 items that do not vary but were provided by PROMIS developers for the many settings where CAT administration is not yet feasible. Since fixed forms provide reliable scores that may not differ substantially from CAT-derived scores, at least for clinical decision-making, the decision of whether to use fixed-forms vs. CAT can be tailored to the health care system's setting and resources[3,[44][45][46][47][48], including the degree to which patient portals enabling self-administration of such measures are implemented among its population.Regarding raw vs. T-scores, the latter are preferable since for all scales, a T-score of 50 is the population norm and every 10 points is one standard deviation. However, conversion of raw to T-scores requires the use of tables which if done manually requires extra clinician time.…”
mentioning
confidence: 99%
“…The fixed form scales typically range from 4 to 8 items that do not vary but were provided by PROMIS developers for the many settings where CAT administration is not yet feasible. Since fixed forms provide reliable scores that may not differ substantially from CAT-derived scores, at least for clinical decision-making, the decision of whether to use fixed-forms vs. CAT can be tailored to the health care system's setting and resources[3,[44][45][46][47][48], including the degree to which patient portals enabling self-administration of such measures are implemented among its population.Regarding raw vs. T-scores, the latter are preferable since for all scales, a T-score of 50 is the population norm and every 10 points is one standard deviation. However, conversion of raw to T-scores requires the use of tables which if done manually requires extra clinician time.…”
mentioning
confidence: 99%
“…More detailed information about the demographic and smoking characteristics of the samples can be found in Stucky et al (in press) and in Table S1 of the online supplementary material.…”
Section: Resultsmentioning
confidence: 99%
“…qualitative methods (Edelen et al, 2012) followed by modern psychometric techniques (e.g., item-factor analysis and item response theory (IRT), Hansen et al, 2014), we identified six unidimensional banks and developed fixed-length short forms (SFs) and dynamic computer adaptive tests (CATs) to measure these distinct constructs among daily and nondaily smokers. The banks’ psychometric properties, including their reliability and initial validity, are reported in a special supplement of Nicotine and Tobacco Research (Hitsman, 2014), and new analyses indicate that the psychometric performance of the banks is sound and comparable across form (SF vs. CAT) and mode of administration (paper and pencil vs. computer; Stucky, Huang & Edelen, in press). …”
mentioning
confidence: 99%
“…Nicotine dependence was assessed by the short form of the Patient-Reported Outcomes Measurement System Nicotine Dependence scale, which has shown acceptable reliability and validity. 24,25 Example item: “I drop everything to go out and buy cigarettes” with responses on a 5-point Likert scale ( never , rarely , sometimes , often , or always ). Responses to the four items were summed (range 4–20).…”
Section: Methodsmentioning
confidence: 99%